Analysis of the ulun tagom concept (putra regional) in lumbis pasiangan office performance management, Nunukan district, North Kalimantan - Lumbis Lumbis; Zainur Hidayat; Nurul Hidayat (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The purpose of this research is to examine and find out the principles of the concept of "Ulun Tagom," which means "Son of the Region," in employee performance management at the Lumbis Pansiangan District Office as a performance appraisal. This study uses a qualitative discrete approach to describe the Ulun Tagom (Son of the Region) phenomenon in employee performance management in Lumbis Pansiangan District by gathering as much information as possible and integrating valid data obtained from interviews, documents, and observations. The results can be concluded: 1) The principle of Ulun Masiog, which in ancient times during the mengayau era meant "knight," is a code of ethics for a group of people who uphold adat and have the determination to protect and look after their people. 2) Amod's Principle Amod can mean creative, innovative, and productive based on honesty and sincerity in carrying out a job. 3) The Atulikas Principle the Atulikas principle emphasizes timeliness in completing work. That is, in carrying out work, the Dayak Agabag indigenous people do a thorough job, must focus, must not procrastinate on work, and do not take work lightly, so that this principle morally influences Ulun Tagom employees in completing work.